PENINGKATAN KEMAMPUAN FISIK MOTORIK KASAR MELALUI KEGIATAN TARI MANUK DADALI UNTUK ANAK USIA 5-6 TAHUN DI TK PGRI 03 SRIGONCO BANTUR-MALANG - Kholifah, Siti Nur; Nurhalimah, Evi (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2019)
The application manuk dadali dance in integrated learning. The purpose of this study is to describe the methods used to improve the physical abilities of gross motor skills of children aged 5-6 years and to find out the activities of manuk dadali dance activities that can improve the physical abilities of fine motor skills of children aged 5-6 years in TK PGRI 03 Srigonco. The research design used was classroom action research using two cycles. Each cycle consists of planning, acting, acting, observing and reflecting. Data collection techniques used were observation techniques in the form of instruments and documentation techniques. The difference between cycle I and cycle II is that in the first cycle the movements taught are not done thoroughly and in the second cycle every meeting of all movements is practiced simultaneously to facilitate observation of children who have not mastered manuk dadali dance movements. This study can be concluded that it can improve the gross motor skills of children aged 5-6 years with visible indicators of success from 53.12% to 79.42% seen an increase between cycles with a percentage of 26.3%..